Moral Education in the Children's Phase in the View of Ibn Sina - Cahya Aulya; Aang Kunaepi; Nasikhin Nasikhin (ARIMA : Jurnal Sosial Dan Humaniora, 2025)
This research discusses moral education in the children's phase which has an important role in forming good personality and character. One of the famous philosophers and scientists, Ibn Sina, has a view on the importance of instilling moral values from the childhood phase. This research focuses on examining Ibn Sina's thoughts on moral education in the children's phase. This study uses a qualitative approach through literature study by analyzing journals related to moral education from Ibn Sina's perspective. The results of the study show that Ibn Sina emphasized that moral education must begin from children through a gradual approach, and in accordance with the development of children